2021
DOI: 10.3889/oamjms.2021.6262
|View full text |Cite
|
Sign up to set email alerts
|

A Qualitative Study Inquiry among Patients with Diabetic Foot Ulcers: What have They Felt?

Abstract: BACKGROUND: Diabetic foot ulcers (DFU) caused physical and psychosocial problems and the risk of amputations and death. AIM: The aim of the study was to overview the feelings of diabetes mellitus patients with DFU. METHODS: A phenomenological qualitative study design was undertaken from January to April 2020. A total of 25 patients with DFU were determined through the purposive sampling technique. The study was conducted among the patients undertaking home-based wound care in Bojonegoro, Indonesia. The pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Self Social support network was also highlighted by participants in facilitating self-care practices. Family members, peers, and community resources have been reported to be sources of encouragement, practical assistance, and emotional support (18,19). Leveraging these social networks can enhance patient engagement and promote sustained behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…Self Social support network was also highlighted by participants in facilitating self-care practices. Family members, peers, and community resources have been reported to be sources of encouragement, practical assistance, and emotional support (18,19). Leveraging these social networks can enhance patient engagement and promote sustained behavior change.…”
Section: Discussionmentioning
confidence: 99%
“…They reported being very distressed about having the DFU and having great fear of lower limb amputation. Previous research exploring the experience of living with DFU has found several symptoms of distress 10,40 and reported that patients often fear amputation more than death. 14 These factors might have contributed to a perceived need for psychological intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The system as a whole is related to the allocation of rights and responsibility. For each social system, the integrative function is focus of its most distinctive properties and processes [18]. Systems must complement, maintain, and enhance both individual motivation and the cultural patterns that create and sustain motivation.…”
Section: Discussionmentioning
confidence: 99%
“…This is evidenced by the study of Kusnanto et al regarding patients with diabetic foot ulcer (DFU). In addition to receiving therapy from medical staff, DFU patients must be able to control their psychological conditions to ensure that their blood sugar is properly regulated [18], [19].…”
Section: Discussionmentioning
confidence: 99%